2016
DOI: 10.1177/1077559515624775
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Implementation Study of Trauma-Focused Cognitive Behavioral Therapy for Adjudicated Teens in Residential Treatment Facilities

Abstract: Adjudicated youth in residential treatment facilities (RTFs) have high rates of trauma exposure and post-traumatic stress disorder (PTSD). This study evaluated strategies for implementing trauma-focused cognitive behavioral therapy (TF-CBT) in RTF. Therapists (N = 129) treating adjudicated youth were randomized by RTF program (N = 18) to receive one of the two TF-CBT implementation strategies: (1) web-based TF-CBT training + consultation (W) or (2) W + 2 day live TF-CBT workshop + twice monthly phone consultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 25 publications
1
58
0
2
Order By: Relevance
“…There have been several calls to develop systems that identify and treat traumatized youth (Berliner & Kolko, 2016;Crosby, 2016;Ko et al, 2008). Interventions such as trauma-focused CBT have led to improved outcomes for adjudicated teens including reduced depression, PTSD, and recidivism (Cohen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several calls to develop systems that identify and treat traumatized youth (Berliner & Kolko, 2016;Crosby, 2016;Ko et al, 2008). Interventions such as trauma-focused CBT have led to improved outcomes for adjudicated teens including reduced depression, PTSD, and recidivism (Cohen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, correctional mental health treatment has been linked to reductions in suicidal ideation, emotional disturbances, and anger (Kaslow & Thompson, 1998;Kendall, Reber, McLeer, Epps, & Ronan, 1990;Underwood & Washington, 2016). Several randomized studies found trauma-focused cognitive behavioral interventions in juvenile justice facilities improved PTSD and depression symptoms among adjudicated youth (Cohen et al, 2016;Ford, Kerig, Desai, & Feirman, 2016). Cognitive behavioral interventions offered in juvenile correctional facilities have also been connected to decreased recidivism (Dowden & Andrews, 1999;Lipsey, 1999;Lowenkamp, Makarios, Latessa, Lemke, & Smith, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…TF-CBT focuses on correcting maladaptive beliefs about the traumatic event, reducing negative emotional reactions to the trauma, and providing caregivers with the tools needed to manage their child’s stress and their own stress. TF-CBT has been used in diverse health settings in the USA [53, 54•, 55] and around the world [56–59, 60••, 61–63]. In one study that included a significant cultural adaptation of TF-CBT, O’Callaghan and colleagues [60••] conducted a randomized controlled trial (RCT) of TF-CBT, the first of its kind to test an intervention specifically for female adolescent victims of sexual violence in a non-Western population, namely, among adolescent Congolese girls who had either witnessed or experienced rape or sexual abuse.…”
Section: Evidence-based Treatments For Ptsd: Beyond the Academic Medimentioning
confidence: 99%
“…One recent comparative effectiveness trial examined a web-based TF-CBT intervention (W) compared to a web-based TF-CBT intervention plus live dissemination (W+L) for adjudicated teens [54•]. Results showed that teens who received both web-based intervention and live intervention experienced significant reduction in PTSD symptoms when compared to the web-only group.…”
Section: Treatment Delivery: Increasing Adoptionmentioning
confidence: 99%
“…There are also PTSD symptoms common in youth (Briere, ; Ehlers & Clark, ; Steinberg et al., ) that are important treatment targets (Cohen, Mannarino, & Deblinger, ; Cohen et al., ; Ehlers & Clark, ) such as physiological reactions and intrusive memories that are not individualized items on the PC‐PTSD. For example, physiological reactions can be an indication of neurobiological symptoms associated with stress response (Cross, Fani, Powers, & Bradley, ), which are often displayed as somatic complaints in youth who have experienced childhood maltreatment (Katon, Sullivan, & Walker, ; Smith & Flannery‐Schroeder, ; Waldinger, Schulz, Barsky, & Ahern, ).…”
mentioning
confidence: 99%